Correct stapling technique in laparoscopic sleeve gastrectomy: Are we increasing the bleeding? A prospective cohort study - DALKILIÇ, MUHAMMED SAİD (My University, 2023)
Introduction: Laparoscopic sleeve gastrectomy (LSG) has become the most common bariatric surgery procedure. Bleeding is the most common complication of this surgery and mostly occurs from the staple line. The aim of this study was to evaluate whether waiting between compression and firing during the stapling phase reduces the postoperative bleeding.Methods: A total of 325 patients who underwent LSG between April and July 2022 were analyzed prospectively. In terms of postoperative bleeding, the two groups, which we waited 30 seconds between staple firings and the no wait group, were compared.Results: The mean age of patients was 37.36 (+/- 11.12) years and mean body mass index was 45.18 (+/- 3.1) kg/m(2). Eleven patients needed transfusion. The rate of haemorrhagic complications was 3.38% (Group 1% 6.21 and Group 2% 1.11) (P = .012). The duration of surgery was similar to 10 minutes longer in the study group, which we waited (P = .0001).Conclusions: During the stapling stage in LSG, waiting between compression and firing can help reduce postoperative bleeding.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery; sleeve gastrectomy; postoperative complications; postoperative hemorrhage; surgical stapling; DUODENAL SWITCH; A SIMPLE; COMPLICATIONS; RESECTION; LEAK